Effect of Ply Orientation on Strength and Failure Mode of Pin Jointed Unidirectional Glass-epoxy Nanoclay Laminates - Singh, Manjeet; Bhunia, H.; Saini, J. S. (Defence Science Journal, 2015)
In the present work the effect of the different ply orientations and nano filler on the bearing strength and failure mode of the pin joints is investigated both experimentally and numerically. Glass-epoxy composite laminates were prepared with [0°/45°/90°], [0°/45°/0°] and [0°/90°/0°] ply orientations. Nanoclay filler with 1, 2, 3, 4 and 5wt% were added in the epoxy for the said orientations to prepare the pin joints. Results show that the strength of the pin joints is drastically dependent on both ply orientations and nanofiller wt%. The joint geometry i.e., the distance from the free edge of specimen to the diameter of the hole (E/D) ratio and width of the specimen to the diameter of the holes (W/D) ratio were also investigated which effected the failure mode of the joints. Tsai-Wu failure theory along with the characteristics curve method was used for the prediction of failure modes numerically.